MEMBUMIKAN MORAL BERPOLITIK NABI MUHAMMAD DI ERA 4.0 - Cut Zaenab (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2022)
Prophet Muhammad is a role model that Allah gave to mankind. Rasulullah teaches human everything that is in accordance with the Qur'an and hadith; included in politic. The politic taught by the Prophet Muhammad had been exemplified by him in its application when the Prophet Muhammad led Mecca and Medina.Rasulullah forming a country could not be separated from the support of the Arab community at that time. Rasulullah also applied correct moral and ethic in politic. However, we find in this 4.0 industrial revolution that everything becomes sophisticated and fast, the officials forget that moral. The leaders are too addicted to power and insane from office, so that they make politics as a bridge to pleasure without seeing the people in distress. Politics taught by the Prophet has been eroded more and more. Liberal official even provide separation on religion and politic. Religious matters are left to be the business of the Ulama and the state should be left to the business of politicians. Basically we already know that religion and state are of course inseparable. Religion must be upheld in politics and as a state; in order to create peace and peace as expected by the whole community.